Bjørn Gerde; Studies on the sarcocyst morphology and life cycles of six species of Sarcocystis from reindeer (Rangifer tarandus) - Skjenneberg (ed.), Sven (Rangifer, 1987)
Bjørn Gjerde successfully defended his thesis for the degree of doctor medicinae veterinariae (Dr. med. vet.) at the Norwegian College of Veterinary Medicine, Oslo, on June 13, 1986.